Extensive Inter-Cyst DNA Methylation Variation in Autosomal Dominant Polycystic Kidney Disease Revealed by Genome Scale Sequencing - Bowden, Sarah A.; Stockwell, Peter A.; Rodger, Euan J.; Parry, Matthew F.; Eccles, Michael R.; Stayner, Cherie; Chatterjee, Aniruddha (Frontiers in Genetics, 2020)
Autosomal Dominant Polycystic Kidney Disease is a heritable disease characterised by bilateral renal enlargement due to the growth of cysts throughout the kidneys. Inheritance of a disease-causing mutation is required to develop ADPKD, which results in end-stage renal disease and is associated with a high morbidity. The pathology underlying cyst formation is not well understood. To address this, we have previously shown the global methylome is altered in ADPKD tissue, suggesting a role of DNA methylation in disease-state renal tissue. As cysts are believed to arise independently, we hypothesise that DNA methylation changes vary accordingly. Here we further investigate the role of DNA methylation within independent cysts to characterise key intra-individual changes. We demonstrate that fragments within CpG islands and gene bodies harbour the greatest amount of variation across the ADPKD kidney, while intergenic fragments are comparatively stable. A proportion of variably methylated genes were also differentially methylated in ADPKD tissue. Our data provides evidence that individual molecular mechanisms are operating in the development of each cyst.